Upaya Penegakan Hukum Kepolisian Terhadap Pelaku Tawuran Antar Pelajar Dihubungkan dengan Undang-Undang Nomor 2 Tahun 2002 Tentang Kepolisian Negara Republik Indonesia (Studi Kasus Wilayah Hukum Kabupaten Karawang) - Nur Elita, Raden Lita; Guntara, Deny; Abas, Muhamad; Targana, Tatang (UNES Law Review, 2023)
There are still fights that continue to occur among students in groups that are free from the supervision of law enforcement, in this case the police. The police must be able to make preventive efforts so that brawls do not occur among students in groups in areas by monitoring areas prone to conflict, providing direction and assistance to schools, parents and the local community. By carrying out supervision and direction, it is believed that brawls among students can be limited. The problems in this research are, first, how is law enforcement by the Karawang Regency regional police against perpetrators of brawls between students linked to Regulation Number 2 of 2002 concerning the State Police of the Republic of Indonesia? , secondly, what factors hinder police law enforcement efforts against perpetrators of brawls between students in the Karawang Regency area? This research uses subjective exploration and in this research the author uses a standard juridical methodology with the main information used being selected information, namely information obtained from writing research, and supporting information in the form of books, papers, articles, legal guidelines, etc. The results of the research are law enforcement efforts against perpetrators of brawls/fights between students in the Karawang area, especially the resolution of brawls, assisted through reformatory and non-punitive efforts, corrective intervention efforts have been completed including schools and students related to the fights and the variables that influence them. Then there are 4 (four) inhibiting factors, namely, law enforcement itself, limited facilities or agencies, lack of active role in prevention efforts from the community and the culture of fighting which has become a habit among students.